Large for Gestational Age Infants and Adverse Outcomes among Uncomplicated Pregnancies at Term - Mendez-Figueroa, Hector; Truong, Van Thi Thanh; Pedroza, Claudia; Chauhan, Suneet P. (American Journal of Perinatology, 2017)
Background While traumatic delivery with large for gestational age (LGA; birth weight above 90%) is acknowledged, there is paucity of data regarding other morbidity and mortality associated with LGA. Our hypothesis was that compared with appropriate for gestational age (AGA), LGA have a significantly higher rate of composite neonatal morbidity (CNM).Objective Our objective was to compare the CNM among uncomplicated LGA versus AGA at term (37 weeks or more) among all available Maternal-Fetal Medicine Units (MFMU) databases. We excluded women who delivered before 37 weeks, those with hypertension or diabetes, multiple gestations, and known anomalies, and those with birth weight less than 10% for GA. Using multivariable analysis, we compared the CNM between LGA and AGA. Random-effect logistic regressions were used to account for study heterogeneity, with adjustment for potential confounders. We calculated adjusted odds ratio (aOR) and 95% confidence intervals (CI).Results Approximately 60% (n = 50,734) of all participants met inclusion criteria. Among uncomplicated pregnancies, the rate of LGA was 12.1%. The rate of CNM was 15% in LGA and 10% in AGA (aOR: 1.58; 95% CI: 1.46–1.70). The likelihood of stillbirth and neonatal mortality was similar among both groups. Subgroup analysis revealed that CNM was increased among both birth weight > 95% and birth weight 90 to 95% and at different GA at delivery.Conclusion Among uncomplicated pregnancies at term, LGA newborns, compared with AGA, have a significantly higher likelihood of CNM but similar stillbirth and neonatal death risk. Trials are warranted to determine appropriate management of LGA to decrease these risks.
Keywords: macrosomia; LGA; morbidity; mortality